Knee Joint Arthroplasty - Cho, Wooshin (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book presents up-to-date knowledge on all aspects of total knee joint arthroplasty (TKA). It opens by considering indications for TKA and implant selection, covering basic science, design, and prosthetic materials. The basic and advanced operative procedures, along with theoretical background, are then described in detail for both primary and revision surgery. The operative techniques for TKA in specific and complex conditions are included. Complications of TKA and their treatment are also discussed, and clear guidance is provided on postoperative management and patient education. The author introduces his personal surgical tips and opinions on controversial issues based on his experience of TKA in some 6,000 cases. Numerous helpful illustrations and radiographs from the author's caseload are presented to assist readers in carrying out the described procedures.